A nomogram for predicting echocardiogram prescription in outpatients: an analysis of the NAMCS database - Liu, Yujian; Deng, Yanhan; Wang, Hongjie; Liu, Wanjun; He, Xingwei; Zeng, Hesong (Frontiers in Cardiovascular Medicine, 2023)
Background and objective Cardiovascular disease is the leading cause of morbidity and mortality globally. Echocardiography is a commonly used method for assessing the condition of patients with cardiovascular disease. However, little is known about the population characteristics of patients who are recommended for echocardiographic examinations. Methods The National Ambulatory Medical Care Survey was a cross-sectional survey previously undertaken in the USA. In this study, publicly accessible data from the National Ambulatory Medical Care Survey database (for 2007–2016 and 2018–2019; data for 2017 was not published) were utilized to create a nomogram based on significant risk predictors. The study was performed in accordance with the relevant guidelines and regulations stipulated in the National Ambulatory Medical Care Survey database. Patients were randomly assigned to one of two groups: training cohort or validation cohort. The latter was used to assess the reliability of the prediction nomogram. Decision curve analysis was performed to evaluate the net benefit. Propensity score matching analysis was used to evaluate the relevance of echocardiography to clinical decision-making. Results A total of 217,178 outpatients were enrolled. Multivariable logistic regression analysis demonstrated that hypertension, hyperlipidemia, coronary artery disease/ischemic heart disease/history of myocardial infarction, congestive heart failure, major reason for visit, metropolitan statistical area, cerebrovascular disease/history of stroke or transient ischemic attack, previously assessed, insurance, referred, diagnosis, and reason for visit were all predictors of echocardiogram prescription in outpatients. The reliability of the predictive nomogram was confirmed in the validation cohort. After propensity score matching, there was a significant difference in new cardiovascular agent prescriptions between the echocardiogram and no echocardiogram groups (P < 0.01). Conclusion In this cohort study, a nomogram based on the characteristics of outpatients was developed to predict the possibility of prescribing echocardiography. The echocardiogram group was more likely to be prescribed new cardiovascular agents. These findings may contribute to providing information about the gap between actual utilizations and guidelines and the actual outpatient practice, as well as meeting the needs of outpatients.